Influence of Biochar Application on Morpho-Physiological Attributes of Tomato (Lycopersicon esculentum Mill) and Soil Properties. Issue 4 (21st February 2023) - Arshad, Usman; Raheel, Muhammad; Ashraf, Waqas; Ur Rehman, Atta; Zahid, Muhammad Salman; Moustafa, Mahmoud; Ali, Muhammad Amjad
ABSTRACT: Biochar amendment has been known as a promising strategy that improves crop productivity and physio-chemical properties of soil. A pot experiment was conducted to investigate the effect of three biochars: wheat straw, sugarcane bagasse, and rice husk at different levels 2%, 3%, and 5% (w/w) on soil properties and growth of tomato cv. "Money Maker." Results revealed that rice husk at 3% concentration showed significant improvement (+37.4–68.6%) in plant height, number of leaves, fresh and dry shoot weight, fresh and dry root weight and root length compared to control. The physiological parameters like stomatal conductance, photosynthesis, transpiration rate, and water use efficiency were also enhanced (+38–62%) in 3% RH-treated plants while chlorophyll contents were highest in 5% WS, whereas cell membrane stability was maximum in 3% WS-treated plants compared with control. Moreover, 3% RH caused a significant increase (+22.4–81.7%) in electrical conductivity, cation exchange capacity, organic matter, organic carbon, nitrogen, phosphorus, and potassium. Conclusively, 3% RH was found to be the best treatment that improved the soil properties and plant physiological traits that led to enhance overall plant growth. Therefore, RH biochar amendment of soil can be potentially utilized for improving soil properties and plant health.